Limb Reconstruction Surgery When There is No Fluoroscopy: Themes for Success - Anirejuoritse Bafor; Emeka Izuagba; Christopher Iobst (Journal of Limb Lengthening & Reconstruction)
Intraoperative fluoroscopy provides high-quality digital imaging that allows real-time visualization of internal body structures. This has several advantages in limb reconstruction surgery: it refines surgical procedures, shortens the duration of surgery, and improves overall treatment outcomes. However, in resource-challenged environments, where the burden of limb deformities and the need for corrective surgery also exist, fluoroscopy may not be available. Therefore, surgeons must develop creative methods to perform surgical procedures safely when working in those settings. This article discusses some of the peculiarities of performing limb reconstruction surgery without a C-arm. It highlights practical modifications that enable surgical procedures to be performed without image guidance and provides a series of cases to illustrate key points.